Parameter θ-Type Marcinkiewicz Integral on Nonhomogeneous Weighted Generalized Morrey Spaces. (16th December 2020) - Lu, Guanghui
Abstract : Let X, d, μ be a nonhomogeneous metric measure space satisfying the upper doubling and geometrically doubling conditions in the sense of Hytönen. In this setting, the author proves that parameter θ -type Marcinkiewicz integral M θ ρ is bounded on the weighted generalized Morrey space L p, ϕ, τ ω for p ∈ 1, ∞ . Furthermore, the boudedness of M θ ρ on weak weighted generalized Morrey space W L p, ϕ, τ ω is also obtained.